Ireland : Ex Post Evaluation of Exceptional Access Under the 2010 Extended Arrangement. (IMF Staff Country Reports; Country Report ;, 2015)
This paper presents an Ex Post Evaluation of the 2010 Extended Fund Facility (EFF) arrangement with Ireland. The Fund approved in December 2010 an exceptional access EFF arrangement for SDR 19.466 billion (2,321.8 percent of quota) in support of Ireland's home-grown program and as part of a broader financing package of Ireland and its European partners. The program focused on addressing the Irish banking crisis to break the adverse feedback loop between banks, the sovereign, and the real sector. It aimed to restore the banking system to health, including by establishing a smaller banking sector with high capital buffers and more stable funding sources; and to secure fiscal sustainability while limiting the near-term demand drag from fiscal consolidation. Large external financing was a key element of the crisis response. Program implementation was very strong. The program succeeded in stabilizing the banking sector and reducing its size, and fiscal developments were also broadly as anticipated. Domestic demand was, however, weaker than programmed and unemployment remained high, amid a very challenging external environment. Program success, including regaining market access at low interest rates, benefitted also from actions at the wider euro area level. The Ex Post Evaluation draws several lessons from Ireland's experience under the EFF: ? The main lessons emerge from what worked well: Strong country ownership, setting (and meeting) realistic and tailored targets were key for success, combined with effective communication and pro-active engagement. Addressing a banking crisis requires strong and credible actions upfront. ? Some areas offer lessons for future program design: While the main pillars of the financial sector program were sound, more proactive and stronger supervisory interventions and other supportive steps could have strengthened banks' balance sheets and bank profitability and helped resolve problem loans; bank recapitalization should be limited to those with viable medium-term business strategies; unsecured and non-guaranteed creditors of failed banks should be bailed in, provided a strategy to ring fence potential systemic risks can be put in place; macro-financial linkages require careful attention and timely steps to limit sovereignbanking sector feedback loops; fiscal policy has to be mindful of debt sustainability but also of domestic demand conditions, and it needs a clear anchor. ? There are also lessons related to Fund policies: Ireland's EFF underscores the importance of addressing shortcomings of the systemic exemption clause in Criterion 2 of the exceptional access criteria; and it suggests the need to explore ways to secure stronger upfront commitments from monetary union authorities, when those are critical for program success.